Perceived barriers and facilitators to attendance for cervical cancer screening in EU member states: a systematic review and synthesis using the Theoretical Domains Framework. Issue 3 (4th March 2022) - Stuart, Gabriella; D'Lima, Danielle
ABSTRACT: Aims: To identify and synthesise peer-reviewed, published literature reporting perceived barriers and facilitators associated with cervical cancer screening attendance in EU member states with organised population-based screening programmes. Methods: Quantitative and qualitative studies reporting perceived barriers/facilitators to attendance for cervical cancer screening were searched for in databases Embase, HMIC, Medline and PsycInfo. Data were extracted and deductively coded to the Theoretical Domains Framework domains and inductive thematic analysis within domains was employed to identify specific barriers or facilitators to attendance for cervical cancer screening. Results: 38 studies were included for data extraction. Five theoretical domains ['Emotion' (89% of the included studies), 'Social influences' (79%), 'Knowledge' (76%), 'Environmental Context and Resources' (74%) and 'Beliefs about Consequences' (68%)] were identified as key domains influencing cervical cancer screening attendance. Conclusion: Five theoretical domains were identified as prominent influences on cervical cancer screening attendance in EU member states with organised population-based screening programmes. Further research is needed to identify the relative importance of different influences for different sub-populations and to identify the influences that are most appropriate and feasible to address in future interventions.